Variable Speed Drive Characterization: Review of Measurement Techniques and Future Trends. (31st July 2013) - Fiorucci, Edoardo; Bucci, Giovanni; Ciancetta, Fabrizio; Gallo, Daniele; Landi, Carmine; Luiso, Mario
Abstract : The significant advances in power electronics have permitted the implementation of sophisticated methods for control of electric motors. Each innovative electrical apparatus for industrial and automotive application must be correctly and exhaustively tested, both during the developing process and finally for the compliance test. The development of a new electrical system should be associated with a parallel design of an ad hoc measurement system, whose performance should be defined according to the features of the system under test. In recent years, the increasing interest for sensorless electric motor drives involved the development and implementation of a wide set of control techniques. This paper reviews the state and the trends of measurement techniques and instruments applied for the experimental characterization of variable speed drives.